Importance Understanding Literacy Finance in Building Sustainable MSMEs - I Gusti Ayu Ratih Namasswar; M. Fais Luthfi Nuryadin; Maria Magdalena Bate’e; Anggie Sundari; Serniati Zebua (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
Objective study This is for increase understanding literacy finance among SMEs to become attention important for development sustainable. Method study This with systematic literature review of four article relevant and appropriate formula problem. Results found exists eight antecedents and four mercy consequently from literacy finance for SMEs. Limitations article This is Still focused on one database only and general discussing MSMEs, so researcher recommend for researcher next in perfect article.Keywords: Literacy Finance, MSMEs and Finance